PENERAPAN METODE YANBU’A DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN ANAK DIDIK TPQ AL-AZHAR PRENDUAN KEPANJEN JEMBER - Siti Lailatul Fitriyah; Nur Aisyah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2021)
This study aims to determine how the implementation of the planning process, the learning process when it takes place, and the evaluation as well as the inhibiting and supporting factors of the yanbu'a method in improving the ability to read Al-Qur'an skills. The yanbu'a method is a very complete and practical way of learning with a simple and practical selection of learning materials and delivery techniques to children that make it easier for students to understand, especially for skills in reading the Al-Qur'an. This research uses a descriptive qualitative approach, the type of data collection uses observation, and interviews to determine the planning process, the learning process when it takes place and the overall evaluation process as well as the inhibiting and supporting factors. The implementation of Al-Qur'an learning using the Yanbu'a method is carried out like learning in general which includes opening activities, core activities and closing activities, while learning evaluations are carried out every day, every volume increase and at the end of the year. The results of this study indicate that learning using the yanbu'a method can improve the ability to read Al-Qur'an skills.